Parasites shape community structure and dynamics in freshwater crustaceans. Issue 2 (4th February 2020) - Friesen, Olwyn C.; Goellner, Sarah; Poulin, Robert; Lagrue, Clément
Abstract: Parasites directly and indirectly influence the important interactions among hosts such as competition and predation through modifications of behaviour, reproduction and survival. Such impacts can affect local biodiversity, relative abundance of host species and structuring of communities and ecosystems. Despite having a firm theoretical basis for the potential effects of parasites on ecosystems, there is a scarcity of experimental data to validate these hypotheses, making our inferences about this topic more circumstantial. To quantitatively test parasites' role in structuring host communities, we set up a controlled, multigenerational mesocosm experiment involving four sympatric freshwater crustacean species that share up to four parasite species. Mesocosms were assigned to either of two different treatments, low or high parasite exposure. We found that the trematode Maritrema poulini differentially influenced the population dynamics of these hosts. For example, survival and recruitment of the amphipod Paracalliope fluviatilis were dramatically reduced compared to other host species, suggesting that parasites may affect their long-term persistence in the community. Relative abundances of crustacean species were influenced by parasites, demonstrating their role in host community structure. As parasites are ubiquitous across all communities and ecosystems, we suggest that the asymmetrical effects we observed are likely widespread structuring forces.